RESISTANCE LITERATURE IN THE BALAI PUSTAKA ERA: A SYMBOLIC STUDY OF THE STRUGGLE AGAINST COLONIALISM - Wicaksono, Andri (Prosiding Konferensi Internasional Kesusasteraan, 2025)
Resistance Literature during the Balai Pustaka Era (1920–1930) was a crucial period in Indonesian literary history, marked by the emergence of works symbolically expressing resistance to Dutch colonial rule. Even if Balai Pustaka was established by the colonial government, the literary works produced during that period also contained messages of resistance and criticism of the colonial system, albeit indirectly. Therefore, this study aims to analyze the forms of resistance in Balai Pustaka's literary works against colonial practices. The method used is descriptive qualitative with a New Historicism approach that focuses on historical symbols, both in thoughts, feelings, and actions. Data collection techniques were carried out through library techniques. The data analysis technique used is qualitative data analysis. The results of the study show that literary works published by Balai Pustaka began to contain messages of resistance against colonialism in the form of symbols. Balai Pustaka's literary works began to foster a sense of nationalism and an awareness of the importance of unity. Resistance Literature in the Balai Pustaka Era was an important period in the history of Indonesian literature that voiced resistance against Dutch colonialism within the context and limitations set by the colonial government. Thus, these works were not only entertaining, but also provided education and aroused the spirit of nationalism.